Gender-based violence committed by women against men in the Kingdom of Eswatini - Phumuzani Mpofu; Lungile Goodness Mamba (International Review of Social Sciences Research)
This study explored the experiences of Eswatini men who face intimate partner violence perpetrated by women. Using a qualitative approach with semi-structured interviews, the research aimed to understand the lived experiences of these men, alongside insights from individuals knowledgeable about the issue. The study employed the bioecological model as a theoretical framework to examine various forms of abuse experienced by men, barriers to seeking help, and potential motivators for seeking assistance. A purposive sample of twenty-five participants was selected for the study. Thematic analysis was used to analyse the data, revealing multiple forms of abusive behaviours such as dominance, emotional manipulation, physical and verbal abuse. The findings highlighted the complex interplay between cultural norms, societal expectations, and the help-seeking behaviours of male victims. The study suggests several potential strategies to address the issue, including programs aimed at reducing stigma and promoting help-seeking behaviours from a familial perspective. It also proposes establishing safe spaces for male victims to report abuse through outreach initiatives led by trusted local organizations or counsellors stationed in accessible locations. Additionally, the study recommended showcasing success stories from rehabilitation programs to offer hope and inspiration to victims and communities.